Photosynthetic and Lipogenic Response Under Elevated CO2 and H2 Conditions—High Carbon Uptake and Fatty Acids Unsaturation - Butti, Sai Kishore; Venkata Mohan, S. (Frontiers in Energy Research, 2018)
Microalgae are some of the most versatile organisms having ability to grow in diverse conditions and utilize both organic and inorganic carbon sources. Microalgal photosynthesis can be employed to transform carbon dioxide (CO2) into essential bioactives and photofuels. In this study microalgae are grown under modified headspace gas compositions resembling the industrial gaseous effluents. Four experimental variations with CO2 + H2 (1:1 V/V), CO2, H2 and Air as the headspace gas were evaluated to determine the photosynthetic efficiency and bioactives production of microalgae. This study reports an enhancement in quantum yield (Fv/Fm: 0.77) and CO2 biosequestration rate (0.39 g.L-1.d-1) under CO2 + H2 headspace gas composition compared to the other experimental variations. The chemoselective functioning of Rubisco under varying gas concentrations was determined, where elevated CO2 conditions negates the oxygenase activity under a high CO2/O2 ratio which enabled higher CO2 sequestration. The enhanced CO2 sequestration and altered redox conditions under the monophasic operation have also led to a higher average degree of unsaturation and carbon chain length of the fatty acids produced. This study provides an approach to augment photosynthetic efficiency and lipogenesis through non-genetic modifications along with the feasibility to cultivate microalgae in integration with industrial flue gases. Exploiting the true potential of microalgae would provide sustenance from climatic changes and environmental pollution while concurrently producing biobased products analogous to the fossil-derived products.